Gut microbiome and host TOR pathway interact to regulate predator-induced aversive memory in Drosophila melanogaster - Hao-Yu Chen; Po-Sheng Wu; Zong-You Li; You-Cheng Liu; Sheng-Rong Yeh; Bi-Chun Duan; Kai-Wen Cheng; Cheng-Chih Hsu; Yen-Ling Chiu; Wang-Tso Lee; Shou-Zen Fan; Pei-Yu Wang (Proceedings of the National Academy of Sciences, 2025)
The gut microbiome has emerged as a key factor influencing a wide range of host physiological processes and behaviors, though the mechanisms behind these effects remain only partially understood. In this study, we explored the role of the gut microbiome in memory regulation using a parasitoid wasp-induced oviposition depression paradigm in Drosophila melanogaster . Our findings show that flies with depleted gut microbiota, either through axenic culture or antibiotic treatment, exhibited significant memory impairments. However, reintroducing the commensal bacterium Lactobacillus plantarum alone was sufficient to restore memory, while coinoculation with Acetobacter pomorum further enhanced memory performance. Hemolymph metabolomic analyses revealed reduced amino acid levels in antibiotic-treated flies, which were linked to impaired Drosophila target of rapamycin (dTOR) signaling. Additionally, genetic manipulation of dTOR or dietary supplementation with branched-chain amino acids either mimicked or rescued the memory deficits caused by antibiotic treatments. These results suggest that the gut microbiome is essential for regulating memory function by maintaining amino acid homeostasis and proper dTOR signaling, with profound implications for advancing knowledge of cognitive regulation.